Texture and structure of cold-rolled and temper annealed sheet of aluminium 1200 (2002)
Aluminium 1200 is the grade of aluminium used for hollowares. It is the good corrosion resistance and ductility of Aluminium 1200 that made it particularly suitable for hollowares. However, there is a need to control the texture of aluminium sheet to be cold rolled in order to obtained optimal condition favourable for metal drawing. This is the rationale for this work. The effect of annealing and cold rolling on texture and struture of Aluminium 1200 sheets has been established. Working on cold rolled reductions of 80%, 84%, 86, 88%, and 92% and annealing temperature of 350C, 400C and 480 C, for 1hrs and 3hrs, Planar and normal anisotropy (that is, measure of crystallographic texture) were calculated from a known relationship. Samples of 80% cold-rolled reduction and heated to temperature 35C for three (3) hours showed the most favourable texture for metal drawing. Thus, crystallographic texture has been found to be determined by the average normal and planar anisotropy of Aluminium 1200 sheet metal which can be controlled by the annealing temperature and degree of previous cold- working. Texture with very low value of average anisotropy (about unity) has been found suitable for aluminium 1200 metal sheet drawing. Although annealing is observed to enhance the preferred orientation for metal drawing, there is the need to control the grain growth associated with it, which can impair the mechanical properties of the sheet.